Geothermal Reservoir Analysis of Mount Rajabasa Kalianda Potency Area using Resistivity Method and Geothermometer - Nandi Haerudin (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
A research has been done to determine geothermal reservoir boundaries of Mount Rajabasa by using 1D sounding and mapping resistivity method. The mapping acquisition data was done by means of Schlumberger configuration for AB/2 = 150 m, AB/2 = 300 m, AB/2 = 450 m and AB/2 = 600 m, next the data was correlated with ID sounding data at 3–2 line and 3–4 line. Geothermal reservoir was found with depth ≤ 450 m with resistivity value is 35 m. The reservoir has been estimated as sandstone tuff which lay in Lampung formation. From 1D sounding correlated at line 3-2 and 3-4 are indicated existing fluid flowed at 20 m under suface. Geothermal reservoir of Mount Rajabasa has temperature 212.08oC and potency of energy is 12.5 MW/Km2. it classified as medium temperature.